Ludoterapia : uma estratégia da pedagogia hospitalar na ala pediátrica do Hospital Universitário da Universidade Federal de Sergipe - Kohn, Carla Daniela (2010)
The present study describes the result of a report experience carried trough in the pediatric ward at the University Hospital of the Federal University of Sergipe, from August 2008 to August 2009. It aims at inside describe the value of the pedagogist s work developed within the scope of Hospital Pedagogy by employing ludotherapy as a pedagogical educational strategy for children and adolescents in hospital. Demonstrating that education and learning are feasible within the hospital and may well contribute toward patient s well being, who may have development compromised, since deprived from characteristic childhood social interactions. The recapture of hospital function along history enable a view upon its present role within society, where the dominance of technical rationality prioritizes the disease to the detriment of the patient, therefore neglecting the integral aspect of human being. The theoretical perspective by Vygotsky and Wallon have justified our knowledge concerning childhood development, since their propositions reassert the need for social interaction and learning regarding the hospitalized child, seeing that even though going through an episode of illness, growth continues and therefore, plans of action that allow for coping with negative effects deriving from hospitalization, become indispensable. In conclusion, the pedagogist s intervention is essential within this environment and the use of ludotherapy as a pedagogical strategy for developing activities, have contributed to excel for the integral attendance to the hospitalized child. Moreover, this work calls on preparatory educational courses in order to provide professionals who shall be able to act withim the hospital environment.